PENGARUH MOTIVASI BERPRESTASI TERHADAP KESIAPAN BELAJAR, PELAKSANAAN PRAKERIN DAN PENCAPAIAN KOMPETENSI MATA PELAJARAN PRODUKTIF - Fatchurrohman, Rudy (INVOTEC, 2011)
This study aims to define the factors that influence the achievement of productive subjects competence in TKR (Light Vehicle Engineering), describe the achievement motivation, learning readiness, and Prakerin or OJT (On Job Training) implementation in connection with the achievement of productive subjects, to determine the effect of achievement motivation on learning readiness and OJT implementation, and to determine the effect of learning readiness and OJT implementation on the competence achievement of productive TKR subjects. The calculation results of correlation and coefficient of determination show that achievement motivation correlates to learning readiness by 0,875, and to OJT implementation by 0,678. Learning readiness correlates to competence achievement of productive subjects by 0,392; OJT implementation correlates to the competence achievement of productive subjects by 0,381; while learning readiness and OJT implementation are correlated by 0,418. The study concludes that there is a significant correlation between achievement motivation, learning readiness and OJT implementation, and therefore there is a need to enhance students’ motivation, especially achievement motivation, so that students’ can have better level of learning readiness and OJT implementation